Is AFTA Trade Creating or Trade Diverting? - Cabalu-Mendoza, Helen; Alfonso, C. (Center for International Business, Montclair State University, 2005)
In this article the changes in trade patterns introduced by the ASEAN Free Trade Area (AFTA) are examined. Variation in growth trends and the shift-and-share methodology are used to identify the impact of trade liberalization under AFTA on intra- and extra-regional commodity trade. Data at the commodity level are used and the results indicate that AFTA had trade creation effects, with little evidence of trade diversion.